Characterization of tea tree essential oil and large‐ring cyclodextrins (CD9–CD22) inclusion complex and evaluation of its thermal stability and volatility. (26th November 2020) - Cao, Chuan; Wei, Dongmei; Xu, Li; Hu, Jinwei; Qi, Jun; Zhou, Yibin
Abstract: BACKGROUND: Although the structure and physicochemical properties of large ring cyclodextrins (LR‐CDs) exhibit unique characteristics, and also possess very strong water solubility and high safety, little is known about the embedding performance of macrocyclodextrin. Encapsulation refers to a complex of tea tree oil (TTO) with the wall material, protecting the core material or changing its properties from adverse external factors, controlling its release rate against the evaporation and degradation of essential oils. In the present study, LR‐CDs complexed with TTO were prepared by co‐precipitation methods. RESULTS: The mass ratio of LR‐CDs‐TTO was six and the maximum complexation efficiency was 86.23%. Fourier‐transform infrared spectroscopy analysis presented the loss of characteristic peaks related to TTO in the complex and no other additional peaks were observed. X‐ray diffraction examination demonstrated several sharp peaks and intensity peaks at the diffraction angle of the TTO‐LR‐CDs complex. 1 H‐NMR indicated a chemical shift as a result of the interaction between the molecules in the inclusion complex. Moreover, the thermal stability and aqueous solubility of TTO were enhanced after synergy with LR‐CDs; particularly, the solubility of the complex was increased by 329‐fold. The volatile characteristics of the encapsulated and original TTO were identical. CONCLUSION: The results of the present study show that TTO was efficaciously complexed with LR‐CDs and exhibited enhanced solubility and thermal stability. © 2020 Society of Chemical Industry